2022
DOI: 10.1039/d2sc00419d
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective [1,2]-Stevens rearrangement of thiosulfonates to construct dithio-substituted quaternary carbon centers

Abstract: An enantioselective [1,2] stevens rearrangement was realized by using chiral guanidine and copper(I) complexes. Bissulfuration of α-diazocarbonyl compounds was developed through using thiosulfonates as the sulfenylating agent . It was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…In 2022, Liu and co-workers systematically studied the asymmetric catalytic [1,2]-Stevens rearrangement reaction for SO 2 -S insertion using chiral guanidine 136 and copper(I) complexes 140 as catalysts and thiosulfonates as the sulfenylating reagents (Scheme 43). 57 The desired chiral dithioketal derivatives 135 could be obtained in good yields (up to 90% yield) with high enantioselectivities (up to 96 : 4 er). Through a series of cross-over experiments, a concerted ionic pathway was proposed: due to the coordination ability of the guanidines, a chiral copper complex catalyst 140 was firstly generated for the addition of the diazo ester 130.…”
Section: S-s Bond Insertionmentioning
confidence: 98%
“…In 2022, Liu and co-workers systematically studied the asymmetric catalytic [1,2]-Stevens rearrangement reaction for SO 2 -S insertion using chiral guanidine 136 and copper(I) complexes 140 as catalysts and thiosulfonates as the sulfenylating reagents (Scheme 43). 57 The desired chiral dithioketal derivatives 135 could be obtained in good yields (up to 90% yield) with high enantioselectivities (up to 96 : 4 er). Through a series of cross-over experiments, a concerted ionic pathway was proposed: due to the coordination ability of the guanidines, a chiral copper complex catalyst 140 was firstly generated for the addition of the diazo ester 130.…”
Section: S-s Bond Insertionmentioning
confidence: 98%
“…Regarding the asymmetric thiosulfonylation, Liu and coworkers recently developed an asymmetric 1,1-thiosulfonylation of α-diazoesters 75a with thiosulfonates 75b through a chiral guanidine/Cu( i ) complex-catalyzed [1,2]-Stevens rearrangement pathway (Scheme 75). 103 A series of chiral dithioketal derivatives 75c was synthesized in good yields with up to 96 : 4 er. It was found that the enantioselectivity of this reaction was positively affected when the steric hindrance of the aniline moiety of guanidines increased.…”
Section: Thiosulfonylationmentioning
confidence: 99%
“…Review / Short Review Furthermore, in 2022 Liu and Feng group furtherly developed the S-S bond insertion by using a novel bifunctional guanidine ligand (Scheme 16). 38 The reaction of diazoesters 35 with thiosulfonates 36 in the presence of copper(I)/chiral acyclic guanidine-amide catalyst afforded S-S bond insertion product 37 in generally good yields with moderate to excellent ees. It was found that, the reaction is sensitive to steric hindrance on sulfur and decreased enantioselectivities were observed when S-ethyl and S-propyl substituted thiosulfonates were used as substrates.…”
Section: Synthesismentioning
confidence: 99%